Patients’ and Providers’ Views on Causes and Consequences of Healthcare Fragmentation in the Ambulatory Setting: a Qualitative Study - Kern, Lisa M. (J Gen Intern Med, 2019)
BACKGROUND: Patients with chronic conditions routinely see multiple outpatient providers, who may or may not communicate with each other. Gaps in information across providers caring for the same patient can lead to harm for patients. However, the exact causes and consequences of healthcare fragmentation are not understood well enough to design interventions to address them. OBJECTIVE: We sought to elicit patients’ and providers’ views on the causes and consequences of healthcare fragmentation. DESIGN AND PARTICIPANTS: We conducted a qualitative study with focus groups of patients and, separately, of providers (attending physicians and nurse practitioners) at an academic hospital-based primary care practice in New York City in June–August 2017. Patient participants were English-speaking adults with ≥ 2 chronic conditions. APPROACH: Each focus group lasted 1 h and asked the same two questions: “Why do you think some patients receive care from many different providers and others do not?” and “What do you think happens as a result of patients receiving care from many different providers?” Data collection continued until a point of data saturation was reached. Thematic analysis was used to identify themes and subthemes. KEY RESULTS: We conducted 6 focus groups with a total of 46 participants (25 patients and 21 providers). Study participants identified 41 unique causes of fragmentation, which originate from 4 different levels of the healthcare system (patient, provider, healthcare organization, and healthcare environment); most causes were not related to medical need. Participants also identified 24 unique consequences of fragmentation, of which 3 were desirable and 21 were undesirable. CONCLUSIONS: The results of this study offer a granular roadmap for how to decrease healthcare fragmentation. The large number and severity of negative consequences (including medical errors, misdiagnosis, increased cost, and provider burnout) underscore the urgent need for interventions to address this problem directly. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-04859-1) contains supplementary material, which is available to authorized users.